Dual-band S-shaped mmWave MIMO antenna system for Ka-band applications - Sanaullah; Abdullah, Mujeed; Hossain, A K M Zakir; Kiani, Saad Hassan (2024)
This article presents a design of novel millimeterwave (mmWave) phased array for fifth-generation (5G) systems. The single element of the array is composed of an S-shaped radiating element backed by a partial ground plane. It is observed from the numerical datathat the designed mmWave antenna offering a wideband response from 22 to 34 GHz. Furthermore, the efficiency and realized gain of the radiating element is noted to be >95% and 4 dBi, respectively. In addition, the antenna provides directional far-field radiation characteristics in the operating bandwidth.